Technological Innovations in Oral Appliance Therapy for Obstructive Sleep Apnea: A Systematic Review of Advancements, Efficacy, and Patient-Centered Outcomes - Baby Jaman; Sanjeev Singh; Saumya Sharma; Priyabrata Jena; Avinash Kumar; Aviraj Gill (The Bioscan, 2025)
This systematic review evaluates recent technological advancements in oral appliance therapy for obstructive sleep apnea, with a focus on design innovations, efficacy, and patient-centered outcomes. Emerging materials, digital manufacturing techniques, and smart sensor integration have substantially improved the comfort, customization, and objective monitoring of mandibular advancement devices, leading to greater patient adherence and satisfaction compared to traditional CPAP therapy. The review synthesizes evidence from January 2018 to June 2025, highlighting that advanced oral appliances achieve clinically meaningful reductions in the Apnea-Hypopnea Index, enhance sleep quality, and offer favorable economic and scalability profiles for healthcare systems. These findings support the expanded use of technologically sophisticated oral appliances as a viable therapeutic option for OSA, especially among individuals intolerant to standard therapies, and underscore the need for further research into long-term safety and personalized device optimization.